Biophysical drivers of fiddler crab species distribution at a latitudinal limit. (31st August 2018) - Peer, Nasreen; Rishworth, Gavin M.; Miranda, Nelson A.F.; Perissinotto, Renzo
Abstract: Traditionally, it is thought that tropical species diversity and abundance decrease with an increase in latitude, responding to a gradient of drivers related to climate or biotic interactions. To investigate this, potential abiotic (soil, water, and biogeographic parameters) and biotic (brachyuran diversity, gastropod density, tree density, meiofauna density and food availability) drivers of fiddler crabs along the east coast of South Africa (26°S - 34°S) were assessed in multivariate models of fiddler crab presence/absence and abundance. Overall fiddler crab presence/absence was most strongly influenced by biotic variables (i.e. brachyuran diversity, gastropod density, and tree density), while abundance was driven largely by sediment grain size and canopy cover (abiotic variables). Specifically, Austruca occidentalis did not have any strong drivers aside from tree density, both Paraleptuca chlorophthalmus and Tubuca urvillei were influenced strongly by sediment grain size, tree density and crab diversity while Gelasimus hesperiae was influenced by a change in latitude, sediment grain size and meiofauna density. Distribution is not always correlated with latitude or latitudinally-driven variables. Biotic factors seem to play a large role in determining whether or not a species inhabits a specific mangrove habitat while, once established, abiotic factors drive density. This study highlights the complexity of drivers affecting species at their distributional limits, an important assessment considering that these populations would likely demonstrate range shifts in response to climate shifts or changes. Graphical abstract: Image 1 Highlights: Latitude explains a low portion of fiddler crab distribution in South Africa. Biotic rather than abiotic factors significantly explain fiddler crab presence. Abiotic factors (grain size and canopy cover) influence fiddler crab abundance.